Population and Species Composition of Rodents and Insectivores in Settlements of the West Kazakhstan Region Located in the Plague Enzootic Territory - V. A. Tanitovsky; A. A. Gabbasov; V. V. Surov; V. G. Meka-Mechenko; Z. Z. Sayakova; N. S. Maikanov (Проблемы особо опасных инфекций, 2024)
The aim of the study was to analyze the abundance, species composition, dissemination of mouse-like rodents and other small mammals in the settlements of the West Kazakhstan Region over the past 6 years and the factors contributing to the change in the numbers in the long-term aspect.Materials and methods. We utilized the data obtained by employees of the Uralsk Plague Control Station, affiliated branch of the Republican State Enterprise “National Scientific Center of Particularly Dangerous Infections named after Masgut Aikimbaev” during a scheduled epizootiological survey of plague foci located in the West Kazakhstan Region.Results and discussion. The average annual number of rodents and insectivores in the settlements on the plague-enzootic territory of the West Kazakhstan Region was 5.1 in spring season, 8.1 in autumn, with 30.0 % occupancy of the facilities. In outbuildings, the number of rodents was three times higher than in residential buildings and amounted to 11.5 (residential buildings – 3.7). The general species composition of small mammals caught in the settlements was represented by seven species, among which the house mouse was a predominant one (97.5 %). The second place was occupied by the small shrew (1.7 %). There is a downward trend in the number of rodents in the steppe foci of plague (over 18 years – an average of 22.0 %). A slight increase in the number of animals by 2.0 % has been registered in the sandy focus.